ON THE NEGATIVE IMPACT OF ACID RAIN ON PUBLIC HEALTH (Western European Journal of Modern Experiments and Scientific Methods, 2024)
This article discusses the problem of acid rain and its negative impact on public health. The analysis of the problem of acid rain is given from the point of view of what consequences this factor can cause in the human body. The article considers the factors that cause acid precipitation in the atmosphere, and also analyzes the problem of acid rain and its negative impact on the environment and public health.